2009
DOI: 10.1007/s12217-009-9132-x
|View full text |Cite
|
Sign up to set email alerts
|

Sessile Drop in Microgravity: Creation, Contact Angle and Interface

Abstract: We present in this paper the results obtained from a parabolic flight campaign regarding the contact angle and the drop interface behavior of sessile drops created under terrestrial gravity (1g) or in microgravity (μg). This is a preliminary study before further investigations on sessile drops evaporation under microgravity. In this study, drops are created by the mean of a syringe pump by injection through the substrate. The created drops are recorded using a video camera to extract the drops contact angles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 15 publications
1
38
0
2
Order By: Relevance
“…Under microgravity, the drop is maintained on the surface mainly due to surface tension forces and is slightly influenced by the gravity fluctuations. We previously confirmed that under microgravity conditions for low surface tension fluids, the drop does not detach from the surface even if the vibration level is high (Brutin et al 2009). The experiments are performed at the plane cabin pressure which is regulated at 835 ± 2 mbar.…”
Section: Rack and The Test Cellmentioning
confidence: 59%
See 2 more Smart Citations
“…Under microgravity, the drop is maintained on the surface mainly due to surface tension forces and is slightly influenced by the gravity fluctuations. We previously confirmed that under microgravity conditions for low surface tension fluids, the drop does not detach from the surface even if the vibration level is high (Brutin et al 2009). The experiments are performed at the plane cabin pressure which is regulated at 835 ± 2 mbar.…”
Section: Rack and The Test Cellmentioning
confidence: 59%
“…The injection mass flow rate is a parameter which has been determined experimentally in microgravity during a previous campaign (Brutin et al 2009), to avoid jet formation at a high mass flow rate. If the mass flow rate is too low, the drop creation time will be important in comparison to the microgravity time (20 s).…”
Section: Rack and The Test Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of interfacial phenomena in microgravity focuses on how an interface acquires and maintains its shape [8][9][10]. For instance, we can see that in the condition of a reduced gravity, droplets assume a spherical shape (see the Figure 1).…”
Section: Microgravity and Interfacial Phenomenamentioning
confidence: 99%
“…In above mentioned literatures, all the experimental and numerical research are carried out under normal gravity. Actually, a different drop spreading behavior in microgravity has been found (Brutin et al 2009). A better understanding and clear knowledge of the physical mechanism of drop spreading in microgravity could widen the applications of liquids drops with the development of space industry.…”
Section: Introductionmentioning
confidence: 99%